Diversity and Universality in Causal Cognition - Andrea Bender; Sieghard Beller; Michael R. Waldmann (Frontiers Media SA, 2021)
Causality is one of the core concepts in any attempt to make sense of the world, and the explanations people come up with shape their judgments, emotions, intentions and actions. This renders causal cognition a core topic for the social as well as the cognitive sciences. In the past, however, research has been split into diverging paradigms, each pertaining to a distinct (sub)discipline and focusing on a specific domain, thus creating a rather fragmented picture of causal cognition. Furthermore, most of this previous research paid only incidental attention to culture as a possibly constitutive factor, leaving important questions unanswered: Is causality always perceived in the same way? Are causal explanations affected by the concepts to which people refer and/or the language they use? Is causal cognition domain-specific, and if so, how does it differ from agency construal? Is causal reasoning always based on the same cognitive mechanisms, or does the cultural background of people shape how they process respective information - and perhaps even their willingness to search for causal explanations in the first place? By soliciting contributions that address questions like these, this research topic aimed at assessing the extent to which causal cognition may vary across species, cultures, or individuals at various stages of their development, and at integrating different perspectives across a broad range of disciplines. Originating from the work of a research group funded by the Center for Interdisciplinary Research (ZiF) at Bielefeld University, Germany, the scope of this research topic was broadened by inviting additional contributions from researchers with expertise in different fields of causal cognition, agency construal, and/or cultural impacts on cognition. In order to fully exploit the potential of cognitive science, we explicitly encouraged submissions from scholars from all its classic sub-disciplines (i.e., anthropology, artificial intelligence, linguistics, neuroscience, philosophy, psychology) as well as scholars from comparative psychology, cognitive archeology, economics, and any other discipline interested in causal cognition. We welcomed empirical findings as well as theoretical contributions, with an emphasis on those factors that do – or may – constrain, trigger, or shape the way in which humans and other primates think about causal relationships and inform us about both the diversity and the universality of causal cognition.